Pengaruh remunerasi dan motivasi terhadap kinerja pegawai - Pomoeng, Olivia D. Y.; Rombeallo, Yulianus M. (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Employee performance has a very important role in the growth of an agency. Performance measurement is used to evaluate what performance results have produced the maximum results from employees. One way to improve employee performance is to provide employees with motivation and appropriate remuneration so that they can produce even better results than before. The purpose of this study was to determine the effect of remuneration and motivation on the performance of KPP Pratama Palopo tax officials. The method used in this research is a quantitative approach. The study's findings are that remuneration has an effect on employee performance with motivation as an intervening variable, and remuneration has an effect on employee performance with motivation as an intervening variable.